Monopoly innovation and welfare effects - Shuntian Yao; Lydia Gan (Kiel Institute for the World Economy (IfW), 2010)
In this paper we study the welfare effect of a monopoly innovation. Unlike many partial equilibrium models carried out in previous studies, general equilibrium models with non-price-taking behavior are constructed and analyzed in greater detail. We discover that technical innovation carried out by a monopolist could significantly increase the social welfare. We conclude that, in general, the criticism against monopoly innovation based on its increased deadweight loss is less accurate than previously postulated by many studies.
Keywords: D50; D60; 330; Monopoly; social welfare; technical innovation; general equilibrium